Perancangan Sistem Informasi Kehadiran Pegawai Menggunakan Kartu Tanda Penduduk (KTP) (Studi Kasus Kantor Kecamatan Ngajum) - Rivano Dwi Sasono (Jurnal Jaringan Telekomunikasi, 2020)
Employee attendance is one of the most important elements in office activities. Attendance is a data collection activity to determine the number of employee attendance. The employee attendance system at the ngajum sub-district office uses fingerprint technology (Fingerprint). This system is indeed very easy and efficient, but in the sub-district office there are several employees who have difficulty carrying out the fingerprint attendance process because the fingerprints are peeled off or have certain diseases make fingerprints smooth. So that the fingerprint attendance (Fingerprint) at the sub-district office is not used and returns to the manual system. The purpose of this research is to design an employee attendance information system to enter and leave by utilizing the National Identity Card or KTP. For checking IDKTP uses the NFC Reader PN532 which is connected to Arduino Uno as a microcontroller, Raspberry pi as a web server, webcam, LCD display, and buzzer as a sign of success in making attendance. Based on the test results it can be concluded, the NFC reader used can read ID KTP in position vertical and horizontal with a distance of less than 16 mm. When there is a mica barrier and a glass barrier the maximum reading distance is less than 14 mm while the plate and aluminum foil barrier cannot be read. The existence of a barrier makes the distance to read the KTP will be reduced.